Perspective application of metabolic treatment (trimetazidine) in patients with left ventricle dysfunction - Banach, Maciej (Przewodnik Lekarza/Guide for GPs, 2006)
Trimetazidine is a derivative of piperazine and selectively inhibits beta-oxidation of fatty acids. It leads to the inhibition of the oxidation of Free Fatty Acids and secondary increases the glucose oxidation. Current guidelines of European Society of Cardiology on the management of stable angina pectoris exactly determine the role of trimetazidine in the pharmacological management in this group of patients. The application of metabolic treatment in patients with left ventricle dysfunction, despite many available outcomes, still requires of the confirmation in large, randomized, placebo controlled, double blind studies. However the researches publishes in 2005 and 2006 years indicate that metabolic treatment will find its proper place still in the next recommendations.